Instructions for the Management of Harvey's Sea Torpedo - Harvey, Frederick (Salt Lake City, UT : Project Gutenberg, 2022)
"Instructions for the Management of Harvey's Sea Torpedo" by Frederick Harvey is a technical manual written in the early 1870s. This publication serves as an instructional guide for naval officers and operators on the use and management of sea torpedoes, a revolutionary weapon system of that era. The book likely addresses the strategic and practical aspects of deploying torpedoes in naval warfare, reflecting the changing dynamics of naval technology during the late 19th century. The book provides detailed specifications for the construction, loading, and operational handling of both large and small torpedoes, emphasizing the importance of precise mechanics for effective usage in combat situations. Harvey outlines essential procedures for launching torpedoes, handling explosive components, and the tactical execution of attacks on enemy vessels. Also included are insights into the strategic deployment of torpedoes, including various attack scenarios against different types of naval vessels, ensuring that operators are well-equipped to manage the complexities of underwater warfare. (This is an automatically generated summary.)
Release date is 2022-04-15
deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Torpedoes